PBX1 haploinsufficiency leads to syndromic congenital anomalies of the kidney and urinary tract (CAKUT) in humans. Issue 7 (7th March 2017) - Le Tanno, Pauline; Breton, Julie; Bidart, Marie; Satre, Véronique; Harbuz, Radu; Ray, Pierre F; Bosson, Caroline; Dieterich, Klaus; Jaillard, Sylvie; Odent, Sylvie; Poke, Gemma; Beddow, Rachel; et al.
Abstract : Background: Congenital anomalies of the kidney and urinary tract (CAKUT) represent a significant healthcare burden since it is the primary cause of chronic kidney in children. CNVs represent a recurrent molecular cause of CAKUT but the culprit gene remains often elusive. Our study aimed to define the gene responsible for CAKUT in patients with an 1q23.3q24.1 microdeletion. Methods: We describe eight patients presenting with CAKUT carrying an 1q23.3q24.1 microdeletion as identified by chromosomal microarray analysis (CMA). Clinical features were collected, especially the renal and urinary tract phenotype, and extrarenal features. We characterised PBX1 expression and localisation in fetal and adult kidneys using quantitative RT-PCR and immunohistochemistry. Results: We defined a 276-kb minimal common region (MCR) that only overlaps with the PBX1 gene. All eight patients presented with syndromic CAKUT. CAKUT were mostly bilateral renal hypoplasia (75%). The most frequent extrarenal symptoms were developmental delay and ear malformations. We demonstrate that PBX1 is strongly expressed in fetal kidneys and brain and expression levels decreased in adult samples. In control fetal kidneys, PBX1 was localised in nuclei of medullary, interstitial and mesenchymal cells, whereas it was present in endothelial cells in adult kidneys. Conclusions: Our results indicate that PBX1 haploinsufficiency leads to syndromic CAKUT as supported by the Pbx1 -null mice model. Correct PBX1 dosage appears to be critical for normal nephrogenesis and seems important for brain development in humans. CMA should be recommended in cases of fetal renal anomalies to improve genetic counselling and pregnancy management.